Changes of MODY signal pathway genes in the endoplasmic reticulum stress in INS-1-3 cells. - Yanan Dong; Shirui Li; Wenhui Zhao; Yanlei Wang; Tingting Ge; Jianzhong Xiao; Yukun Li (PLoS ONE, 2018)
Objective Metabolic disturbances induce endoplasmic reticulum stress (ERS) in pancreatic beta cells. This study aims to investigate whether a common pathway exists in the ERS induced by various chemicals, including high levels of glucose and palmitate in INS-1-3 cells. Method ERS in INS-1-3 cells was induced by exposure cells to thapsigargin (TG), tunicamycin (TM) or palmitic acid (PA) +high glucose (HG). Digital gene expression (DGE) profiling technique was used to detect differentially expressed genes. The profile of gene expression was detected by gene oncology (GO) function and pathway enrichment analysis. Nkx6.1 over-expression was established in INS-1-3 cell lines by lentivirus infection to revert the inhibition of Nkx6.1 expression found in the situation of ERS. Real time reverse transcription polymerase chain reaction (RT-PCR) was used to verify the expression changes of key genes. Cell viability was measured by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The apoptosis was determined by flow cytometry. INS-1-3 cell function was measured by glucose stimulated insulin secretion test(GSIS). Results As compared to control, DGE demonstrated that there were 135, 57 and 74 differentially expressed genes in TM, TG and HG+PA groups, respectively. Those differentially expressed genes were enriched to ERS, antigen processing and presentation, protein export pathways, and interestingly, the maturity onset diabetes of the young (MODY) pathway. Nkx6.1 is one of common down-regulated gene in MODY signaling pathway among TM, TG and HG+PA groups. Over-expression of Nkx6.1 ameliorated glucolipotoxicity induced apoptosis rate by 45.4%, and increased proliferation by 40.9%. At the same time, GSIS increased by 1.82 folds. Conclusions MODY pathway genes expression was changed in the state of ERS. Over-expression of Nkx6.1 protected the INS-1-3 cells from glucolipotoxicity.